A mutation in THREONINE SYNTHASE 1 uncouples proliferation and transition domains of the root apical meristem: experimental evidence and in silico proposed mechanism - García Gómez, Monica L.; Reyes Hernández, Blanca Jazmín; Sahoo, Debee P.; Napsucialy-Mendivil, Selene; Quintana-Armas, Aranza X.; Pedroza-García, José A.; Shishkova, Svetlana; Torres-Martínez, Héctor H.; Pacheco-Escobedo, Mario A.; Dubrovsky, Joseph G. (Development, 2022)
A continuum from stem to transit-amplifying to a differentiated cell state is a common theme in multicellular organisms. In the plant root apical meristem (RAM), transit-amplifying cells are organized into two domains: cells from the proliferation domain (PD) are displaced to the transition domain (TD), suggesting that both domains are necessarily coupled. Here, we show that in the Arabidopsis thaliana mto2-2 mutant, in which threonine (Thr) synthesis is affected, the RAM lacks the PD. Through a combination of cell length profile analysis, mathematical modeling and molecular markers, we establish that the PD and TD can be uncoupled. Remarkably, although the RAM of mto2-2 is represented solely by the TD, the known factors of RAM maintenance and auxin signaling are expressed in the mutant. Mathematical modeling predicts that the stem cell niche depends on Thr metabolism and that, when disturbed, the normal continuum of cell states becomes aborted.
Gesehen am 05.09.2023